A conversation with Chuck McManis. - O'Hanlon, Charlene (New York ACM, 2006)
Developing systems with a purpose--do one thing, and do it well.
Keywords: General literature; General; Information systems; Information storage and retrieval; On-line information services; Web-based services; Miscellaneous